Modern Spectroscopy - Cooper, Ryan (United States : NY Research Press, 2021)
Spectroscopy is the study of the absorption and emission of light and other radiation by matter as related to the dependence of these processes on the wavelength of the radiation. On the basis of the nature of interaction between the energy and the material, it can be classified into various types. A few of such types are absorption spectroscopy, emission spectroscopy, impedance spectroscopy and resonance spectroscopy. Spectroscopic analysis has contributed significantly to various areas of study within physics such as quantum mechanics, quantum electrodynamics, and special and general theories of relativity. The topics included in this book on modern spectroscopy are of utmost significance and bound to provide incredible insights to readers. Also included herein is a detailed explanation of the various concepts and applications of spectroscopy. Scientists and students actively engaged in this field will find this book full of crucial and unexplored concepts.
Includes index.
Includes bibliographical references.
Keywords: Atomic spectroscopy; Molecular spectroscopy; Spectrum analysis